Thermal stability and luminescence of novel garnet-type yafsoanite Ca3Zn3(TeO6)2:Sm3+ phosphors for white LEDs. Issue 9 (1st May 2021) - Zhang, Lixia; Chen, Shigao; Zhao, Shoucheng; Guo, Jiang; Lv, Qiuyi; Wang, He; Deng, Bin; Zhang, Gongguo; Yu, Ruijin; Geng, Huiling
Abstract: In this study, novel garnet-type yafsoanite tellurate Ca3 Zn3 (TeO6 )2 :Sm 3+ phosphors are successfully synthesized using the traditional high-temperature solid-state reaction. The phase purity of the obtained phosphors is analyzed by X-ray diffraction and Rietveld refinement studies. Morphological variations are also observed with the different concentrations of Sm 3+ ions substitution, which is analyzed using Scanning Electron Microscopy (SEM). The photoluminescent properties of the phosphors are systematically investigated. Results show that the samples display the strongest emission peak at 612 nm under the near-ultraviolet (n-UV) 409 nm excitation. This peak can be ascribed to the 4 G5/2  →  6 H7/2 transition of Sm 3+ . The Ca3 Zn3 (TeO6 )2 :Sm 3+ phosphor shows a high color purity, exhibits excellent thermal stability and good color drifting resistance. Furthermore, red and white light-emitting diodes have been successfully prepared. The white light-emitting diodes (w-LEDs) demonstrates a high color rendering index (CRI, Ra ) and low correlated color temperature (CCT). This study introduces a new orange-red-emitting phosphor and discusses its application in herb-growth w-LEDs.